2010
DOI: 10.1115/1.4002937
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Measurements of Torsion-Tension Coupling in Human Cadaveric Femurs

Abstract: The mechanical behavior of human femurs has been described in the literature with regard to torsion and tension but only as independent measurements. However, in this study, human femurs were subjected to torsion to determine if a simultaneous axial tensile load was generated. Fresh frozen human femurs (n=25) were harvested and stripped of soft tissue. Each femur was mounted rigidly in a specially designed test jig and remained at a fixed axial length during all experiments. Femurs were subjected to external a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…43 A previous study also demonstrated no left-versus-right difference in human cadaveric femurs concerning the simultaneous mechanical coupling of torsion and tension. 16 Twelve of the 16 human femurs had normal bone quality. Although the data can help researchers better understand the nature of femoral bone injury in those with healthy bone, a deeper understanding of the behaviour of osteoporotic or osteopenic bone has not been gained.…”
Section: Limitationsmentioning
confidence: 99%
“…43 A previous study also demonstrated no left-versus-right difference in human cadaveric femurs concerning the simultaneous mechanical coupling of torsion and tension. 16 Twelve of the 16 human femurs had normal bone quality. Although the data can help researchers better understand the nature of femoral bone injury in those with healthy bone, a deeper understanding of the behaviour of osteoporotic or osteopenic bone has not been gained.…”
Section: Limitationsmentioning
confidence: 99%
“…A population group or individual may show nominally different geometry from side-to-side for the lower limbs, 50 but there are no statistical differences between the mechanical properties of left versus right femurs. 5153…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic longbones are gaining more widespread use due to advantages they provide over cadaveric specimens. The use of artificial or synthetic femurs has a sufficiently established history in biomechanics studies [45,81,[122][123][124][125][126][127] because of their similar axial vs. torsional stiffness ratio [128], cancellous and cortical screw pullout shear stress [129,130], and identical failure mechanism under axial compression compared to human femurs [131].…”
Section: Testing Methods In Biomechanical Analysismentioning
confidence: 99%